468 Management of Acute Appendicitis During the Early Phase of the COVID-19 Pandemic: A Single NHS Centre Study. (4th May 2021) - Buksh, M; Jabri, Y; Al Samaraee, A
Abstract: Introduction: Early during the COVID-19 pandemic, surgeons were advised to use conservative management/open surgery for appendicitis. This single-centre study has explored the resulted management differences. Method: Retrospective study covering Prepandemic-data over March-May, 2019 & Pandemic-data over March-May, 2020. Results: Prepandemic-(43 patients): Mean age was 38.3 years. Mean length-of-stay was 1.7 days. Preoperative imaging was used in 32(74.4%) patients; this was diagnostic in 28(87.5%). Non-surgical management was used in 4(9.3%) patients; one needed surgery eventually. Surgical approaches in 40 patients were (laparoscopic: 38(95%), open: 2(5%)). Neither significant morbidity nor mortality was reported. Pandemic-(35 patients): Mean age was 31.2 years. Mean length-of-stay was 2.2 days. Preoperative imaging was used in 30(85.7%) patients; this was diagnostic in 26(86.6%). Non-surgical management was used in 8(22.9%) patients; one needed surgery eventually. Surgical approaches in 28 patients were (laparoscopic: 10(35.7%), open: 18(64.3%)). Neither significant morbidity nor mortality was reported, apart from one patient with COVID-19 postoperative infection. Conclusions: There was a tendency towards conservative approach/open surgery during the pandemic. Though this was statistically significant (p < 0.05), the total number of patients was small to achieve stronger conclusions. Laparoscopy was selectively used during the pandemic where the benefit outweighed the risks.